Therapeutic potential of blocking GAPDH nitrosylation with CGP3466b in experimental autoimmune encephalomyelitis - Godfrey, Wesley H.; Hwang, Soonmyung; Cho, Kaho; Shanmukha, Shruthi; Gharibani, Payam; Abramson, Efrat; Kornberg, Michael Davin (Frontiers in Neurology, 2023)
Multiple sclerosis (MS) is a neuroinflammatory disease of the central nervous system (CNS). Although classically considered a demyelinating disease, neuroaxonal injury occurs in both the acute and chronic phases and represents a pathologic substrate of disability not targeted by current therapies. Nitric oxide (NO) generated by CNS macrophages and microglia contributes to neuroaxonal injury in all phases of MS, but candidate therapies that prevent NO-mediated injury have not been identified. Here, we demonstrate that the multifunctional protein glyceraldehyde-3-phosphate dehydrogenase (GAPDH) is robustly nitrosylated in the CNS in the experimental autoimmune encephalomyelitis (EAE) mouse model of MS. GAPDH nitrosylation is blocked in vivo with daily administration of CGP3466b, a CNS-penetrant compound with an established safety profile in humans. Consistent with the known role of nitrosylated GAPDH (SNO-GAPDH) in neuronal cell death, blockade of SNO-GAPDH with CGP3466b attenuates neurologic disability and reduces axonal injury in EAE independent of effects on the immune system. Our findings suggest that SNO-GAPDH contributes to neuroaxonal injury during neuroinflammation and identify CGP3466b as a candidate neuroprotective therapy in MS.